VARIABILITY OF SEA TEMPERATURE ON THE DEPTH IN THE EVENT OF MADDEN JULIAN OSCILLATION IN INDONESIA MARITIME CONTINENT - Fadhilah M Idris, Rahmi
The purpose of this study is to identify the role of the Madden-Julian oscillation (MJO) in ocean temperatures in Maritim Continent Indonesia (MC) based on 6 years of OLR data, 850 hPa winds, and vertical sea temperatures to a depth of 300 m Hycom simulations from 2012-2018. MJO events have been identified as many as 20 MJO events that were produced for 6 years between 2012 and 2008, 12 events MC crossing and reached the Western Pacific Ocean and 8 MJO events non MC crossing, There were more MC crossing during El Niño than La Niña. This can be attributed to the 2015 El Niño incident being very strong and the short scope of research. The response of the water temperature at MC due to the propagation of MJO is displayed in 2 events, event MC crossing and event non MC crossing. The response of vertical temperatures in MC waters to MJO varies in three locations, the South Java Sea, the Sulawesi Sea and the Banda Sea. The results of the lag correlation test when the MJO period MC crossing shows the effect of changes in SST in South Java to Sulawesi and Banda, while when non MC crossing there is no influence between the South Java SST to Sulawesi and Banda SST.